Improving freeze-thaw stability and 3D printing performance of soy protein isolate emulsion gel inks by guar & xanthan gums. (March 2023) - Yu, Jie; Li, Dong; Wang, Li-jun; Wang, Yong
Abstract: Frozen storage of 3D printing inks could increase their shelf life. We improved freeze-thaw stability and 3D printing performance of soy protein isolate (SPI) emulsion gel inks by guar (GG) and xanthan gums (XG). Freeze-thawed inks led to higher storage modulus ( G′ ), lower water holding capability (WHC) and poor printing performance compared to initial inks. An increase in gums content decreased oil droplet aggregation and protein flocculation in all freeze-thawed inks, hence reducing syneresis in the gel structure and preventing solid-liquid separation during 3D printing. The freeze-thaw stability of SPI-XG inks was consistently greater than that of SPI-GG inks at the same concentrations, resulting in superior 3D printing performance. The hardness of cylinders printed with SPI-XG0.5 freeze-thawed inks was lower than that of the cylinders printed by initial inks, in contrast to the results of G' . At the maximum strain amplitude (500%), Lissajous analysis indicated that the SPI-XG0.5 freeze-thawed inks retained less energy than the initial inks, resulting in a weaker gel. Overall, this study demonstrated that freeze-thaw treatment negatively affected the 3D printing performance of SPI emulsion gel inks, but that the 3D printing performance of freeze-thaw inks could be reinforced by modifying the formulation. Graphical abstract: Image 1 Highlights: Freeze-thaw cycles led to higher G′ and lower 3D printing performance for the inks. Increased gum content inhibited freeze-thawed inks' solid-liquid separation during 3D printing. SPI-XG0.5 inks' 3D printed objects had the highest shape retention in all freeze-thawed inks. SPI-XG0.5 freeze-thawed inks exhibited a weaker gel compared to initial inks during 3D printing.